Economic Evaluation of Family Planning Interventions in Low and Middle Income Countries; A Systematic Review. - Neily Zakiyah; Antoinette D I van Asselt; Frank Roijmans; Maarten J Postma (PLoS ONE)
Background A significant number of women in low and middle income countries (L-MICs) who need any family planning, experience a lack in access to modern effective methods. This study was conducted to review potential cost effectiveness of scaling up family planning interventions in these regions from the published literatures and assess their implication for policy and future research. Study design A systematic review was performed in several electronic databases i.e Medline (Pubmed), Embase, Popline, The National Bureau of Economic Research (NBER), EBSCOHost, and The Cochrane Library. Articles reporting full economic evaluations of strategies to improve family planning interventions in one or more L-MICs, published between 1995 until 2015 were eligible for inclusion. Data was synthesized and analyzed using a narrative approach and the reporting quality of the included studies was assessed using the Consolidated Health Economic Evaluation Reporting Standards (CHEERS) statement. Results From 920 references screened, 9 studies were eligible for inclusion. Six references assessed cost effectiveness of improving family planning interventions in one or more L-MICs, while the rest assessed costs and consequences of integrating family planning and HIV services, concerning sub-Saharan Africa. Assembled evidence suggested that improving family planning interventions is cost effective in a variety of L-MICs as measured against accepted international cost effectiveness benchmarks. In areas with high HIV prevalence, integrating family planning and HIV services can be efficient and cost effective; however the evidence is only supported by a very limited number of studies. The major drivers of cost effectiveness were cost of increasing coverage, effectiveness of the interventions and country-specific factors. Conclusion Improving family planning interventions in low and middle income countries appears to be cost-effective. Additional economic evaluation studies with improved reporting quality are necessary to generate further evidence on costs, cost-effectiveness, and affordability, and to support increased funding and investments in family planning programs.